Resemblance. Issue 4 (April 2017) - Cowling, Sam
Abstract: Our ordinary judgments and our metaphysical theories share a common commitment to facts about resemblance. The nature of resemblance is, however, a matter of no small controversy. This essay examines some of the pressing questions that arise regarding the status and structure of resemblance. Among those to be discussed in what follows: what kinds of resemblance relations are there? Can resemblance be analyzed in terms of the sharing of properties? Is resemblance an objective or subjective matter? What, if any, resemblance facts are fundamental? How does resemblance relate to naturalness?